Economic assessment of some pre-emergence herbicides in the production of millet-cowpea intercrop in the Sudan Savanna Zone of Nigeria - Teli, I. A.; Gworgwor, N. A.; Joshua, S. D.; E. O. Imoloame, E. O. Imoloame (Global Journal of Food and Agribusiness Management, 2012)
Field trials were conducted in 1997 and 1998 cropping seasons at the University of Maiduguri Teaching and Research Farm located in Maduguri (11° 50’N; 13° 10’E). The aim was to carry out an economic analysis of the use of some pre-emergence herbicides for the production of millet-cowpea intercrop. The experiment consisted of 14 treatments which included four different herbicides at three rates each, namely, metolachlor + metobromuron (Galex), metolachlor (Dual), atrazine, and metolachlor + atrazine (Primextra) applied at the rates of 0.5, 1.0 and 1.5 kg a.i./ha, weeding at 3 and 6 weeks after sowing (WAS) and a control plot (weedy check). The treatments were laid out in randomized complete block design (RCBD) replicated three times. Results showed that metolachlor + atrazine (Primextra) at 1.0 kg a.i./ha significantly increased individual and combined yields of cowpea and millet in the two years of study, which were comparable to hoe weeding in two years of study. Also metolachlor + atrazine at 1.0 kg a.i./ha was found to be more profitable, economical and beneficial than two hoe weeding and the other treatments in the two years of study. Therefore for higher yield and economic returns, metolachlor + atrazine (Primextra) at 1.0 kg a.i./ha is recommended to the farmers as alternative to two hoe weeding in the Sudan Savanna Zone of Nigeria.